Оценка возможных внешнеполитических и экономических последствий для Украины в вариантах интеграции с ЕС и ЕЭП - Эминов, Руслан Диляверович; Емінов, Руслан Діляверович; Eminov, Ruslan D. (Одеса : Фенікс, 2014)
В данной статье рассматривается целый комплекс факторов, прежде всего экономического характера, которые стимулируют привлекательность интеграционных процессов для Украины и мотивируют политические решения в отношении анализа и планирования интеграционных намерений Украины в контексте Евразийской и Европейской перспектив. На базе количественного и сравнительного подходов в статье предпринята попытка очертить обзор сценарных перспектив Украины с целью получения максимально объективных данных в экономическом блоке проблемы и преимуществ той или иной формы интеграции для Украины.

In the given article analyzed a complex of the problems which is challenged Ukrainian state in process of building their own model of the partnership policy, which we can title as integration policy in both EAEC and EU direct. The observed components of Ukrainian integration policy mainly are based on the economic and technological factors which in turn stimulates the research a most appropriate form integration of Ukraine as into Eurasian Economic Community, as well as the European Union on the principles of equality an economic attractiveness. Also the author haven’t right to argue that what was done by him is never done before, but in part of realizing the searching work in this domain there are lack of quantitative effects from any version of a similar investigation on such topic. This is why we have a honor to announce that made up article summarize a complicated methods of quantitative and systematic-functional approaches in learning the key aspects of integration policy to both sides. We contemplate the Ukrainian integration’s fate as long time don’t solved node according its own history, and recipe to overcome the intention-lacking state isn’t a question of today this is because the Ukraine government leaders aren’t submitted a wider-scale national plan on accomplishment the most optimal integration policy for all period of its independent life. According this matter the crux of this investigative work is to dive at the core integration process of Ukrainian general policy and examine the most crucial problems which occur during all time. All methods applied in this work is to simplify for the widely readers don’t reducing the scientific evaluation and significance of the concerning topic. For the truth sake it is need to confess that mentioned number of made investigations on this direct unfortunately aren’t include quantitative and qualitative effects of Ukraine movements into European Union as well as there isn’t any arguments and incentives so far which could proves necessity any choice of strategic line of young Ukrainian republic.

У даній статті розглядається цілий комплекс факторів, перш за все економічного характеру, які стимулюють привабливість інтеграційних процесів для України та мотивують політичне рішення щодо аналізу та планування інтеграційних намірів України в контексті Євразійської та Європейської перспективи. На базі кількісного та порівняльного підходів у статті започаткована спроба окреслити огляд сценарних перспектив України з метою одержання максимально об’єктивних даних в економічному блоці проблеми та переваг тієї або іншої форми інтеграції для України.
Эминов Р. Д. Оценка возможных внешнеполитических и экономических последствий для Украины в вариантах интеграции с ЕС и ЕЭП / Р. Д. Эминов // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий [та ін.] ; НУ «ОЮА», Південноукраїнський центр гендерних проблем. – Одеса : Фенікс, 2014. – Вип. 53. – С. 104-114.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; украинская интеграция в ЕС; украинская интеграция в ЕЭП; интеграционная политика Украины; Единое Экономическое Пространство; базовый сценарий развития украинской экономики; зона свободной торговли СНГ; українська інтеграція в ЄС; українська інтеграція в ЄЕП; інтеграційна політика України; Єдиний Економічний Простір; базовий сценарій розвитку української економіки; зона вільної торгівлі СНД; Ukrainian integration into the EU; Ukrainian integration in the Single Economic Space; integration of Ukraine; baseline scenario of the Ukrainian economy; CIS free trade zone